Estrés y su incidencia en el rendimiento cognitivo de una paciente adulta mayor de 75 años de la ciudad de Babahoyo - Castro Barzola, Noelia Nataly (2023)
Stress is a physiological and emotional response of the human body to situations that are perceived as threatening or challenging. This response is part of the body's survival mechanism and can be triggered by situations ranging from a difficult school assignment to a medical emergency. On the other hand, Cognitive performance refers to the brain's ability to process information and perform various cognitive tasks, such as perception, attention, memory, thinking and reasoning, This case study seeks to describe the incidence of stress on the cognitive performance of an older adult patient in the city of Babahoyo. A type of correlational research and mixed approach is applied, implementing techniques such as observation, interview and psychological assessment instruments such as medical history; and psychological tests to measure both variables, the DASS - 21 scale, Holmes and Rahe stress scale, Montreal cognitive assessment, in order to obtain a structural diagnosis of the patient. Based on all the data collected through the psychological evaluation, a therapeutic scheme under Aaron Beck's cognitive-behavioral approach is proposed to help in the management of the signs and symptoms presented by the patient. The results obtained indicated a relevant incidence of stress on the cognitive performance of the elderly patient. Being the death of her spouse and older brother the initial stressors, with these events originated adaptation problems that directly influenced the cognitive abilities such as attention and memory of the older adult.